Comprehensive Systems Design: A New Educational Technology
IX, 436 p.
Keywords: Educational technology in the broadest sense is knowledge and competence forimproving the educational process: for using hardware (equipment), software (methods), and "underware" (underlying organizational structures). This volume in the Special Programme on Advanced Educational Technology presents the results of a NATO Advanced Research Workshop on educational systems design as a new educational technology. The objective of the workshop was toadvance our knowledge about the comprehensive systems design approach for improving educational systems. The workshop was organized for the transdisciplinary interaction of three scientific groups representing design science, organizational/systems science, and educationaltechnology. Participants were selected based on their scholarship as members of one or more of these three groups. The book opens with theframing papers sent by the editors to participants prior to the workshop, then presents five sets of thematic contributions: the conceptual and empirical contexts of comprehensive systems design, the systems design focus, a systems view of designing educational systems, the educational context of systems design, and high technology focus in systems design.